(3TQM JHUQI GdeJYdejf (B((3aj abg GdEeGejI(B)s - (3eMeO LYaQ Hf eMeO Ydj H eMeO HGbQ GdCUagGfj GdHgHgGfis; (3GHf GdeWgQ GdMdj , LeGd GdOjf , CHh efUhQ,J (B726 (3g` s
(3ChdgG (B:s
(3ajbhd GdYHO GdLGfi eMeO LYaQ GdHgHgGfi s
(3BNQgG (B:s
(3jYfi JfTja GdHFQ QCkS GdeSJdRe dfRM LejY GdeGA GdPi bP s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B303s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis